Impianti e sostituti meniscali - Olivieri, M.; Chicon Paez, D.; Turelli, L. (Lo Scalpello - Journal, 2019)
MENISCAL IMPLANTS AND SUBSTITUTES When meniscal lesions occur, preservation of meniscal tissue and restoration of the normal meniscal biomechanics is imperative to avoid early knee osteoarthritis; however, current surgical treatments for meniscal tears suffer from subsequent cartilage degeneration and inconsistent post-treatment results. When meniscal replacement is indicated, the desired implant should be chondroprotective; nevertheless, long-term effects of meniscal transplantation in protecting the articular cartilage have not been fully elucidated as yet. To date, three clinical scaffolds that allow 3-dimensional reconstruction of the meniscal structure (Menaflex CMI, Actifit® scaffold and NUsurface® Meniscus Implant) are available on the market for use, but additional data are needed to properly evaluate their safety and effectiveness.